Feasibility of using a single transmission factor for the Integral Quality Monitor ® on dynamic 15 MV photon beams. (December 2020) - Ade, Nicholas; du Plessis, F.C.P.
Abstract: Purpose: To investigate the feasibility of using a single transmission factor (TF) to account for the attenuation of the iRT Systems Integral Quality Monitor (IQM) on dynamic 15 MV photon beams supported by Gafchromic EBT3 film measurements in a realistic pelvic prosthesis phantom. Materials and methods: IQM TFs for 2 × 2 to 20 × 20 cm 2 15 MV photon beams produced by an Elekta Synergy linac were measured with a 0.6 cm 3 cylindrical chamber inside RW3 phantom slabs. A Monaco treatment planning system (v. 5.00.00) that uses the X-ray voxel Monte Carlo algorithm was used to generate intensity-modulated radiotherapy (IMRT) and volumetric-modulated arc therapy (VMAT) plans in a computed tomography scanned-based model of the pelvic phantom. The phantom was irradiated according to the plans with and without the IQM mounted on the linac. In each case, the absorbed dose in the phantom was measured with EBT3 Gafchromic film. In a second step each plan was re-scaled to new monitor units (MUs) taking into account the IQM TF. The phantom was irradiated according to the plans that now have the re-scaled MUs. Again, film dosimetry was performed with the IQM mounted to the linac. Monaco dose values were compared with film measurements using percentage differences and gamma index criteria of 3%/3 mm. Results: The measured IQM TFs varied within 0.1% over the range of fields evaluated. For the treatment plans, inside the target area, dose differences ≥4% were found between Monaco and EBT3 film for plans with unscaled MUs with the IQM mounted. Plans delivered with unscaled MUs without the IQM as well as plans delivered with scaled MUs with the IQM showed dose differences within 2% between Monaco and film. In these cases, the corresponding gamma pass rate between Monaco and film data was ≥90%. Conclusion: A single TF is sufficient to scale MUs of IMRT/VMAT plans so that the attenuation in IQM is taken into account for dynamic 15 MV photon beams. Dose differences between corrected plans and film measurements are then within 2%, as opposed to ≥4% when not taken into account. Highlights: We investigated the impact of a static-field TF of the IQM on dynamic 15 MV beams. The variations between the IQM TFs with field size were within 0.1%. Attenuated dose for original plans with the IQM mounted was ≥4%. For scaled plans taking into account the IQM TF, the attenuation reduced to 2%. For dynamic beams, a single TF that takes the IQM attenuation into account.